Studies on the growth and characterization of rare-earth Gd-Doped InGan/Gan magnetic semiconductor heterostructures - Mohd Tawil, Siti Nooraya (2011)
Spintronics is an emerging field in which the spin of carriers in addition to the charge of carriers can be used to achieve new functionalities in electronic devices. The availability of materials exhibiting ferromagnetism above room temperature is prerequisite for realizing such devices. Materials suitable for spintronic applications are desired to be compatible with conventional growth and fabrication techniques in addition to exhibiting above room temperature ferromagnetic properties. In this research, the growth of InGaGdN epilayers have been achieved on (0001) sapphire substrates or metalorganic vapor phase epitaxy (M0VPE)-grown GaNIsapphire templates by plasma-assisted molecular beam epitaxy (MBE) using elemental Ga, In, Gd and Si (co-doping) and gaseous N 22 as sources. Magnetic characterization of the grown epilayers was performed by a superconducting quantum interference device (SQUID) magnetometer. Ferromagnetic properties were observed at room temperature for this new type of quaternary alloy material. Co-doping of InGaGdN with Si was performed and increase in shallow donor density as well as enhancement in ferromagnetic properties were achieved. Luminescence properties of InGaGdN were also observed at room temperature with the emission peak energy red-shifts corresponding to the InN molar fraction. Gd incorporation into InGaN epilayers were confirmed by X-ray absorption fine structure (XAFS) analysis revealing that ~ dd??'' ions substitutionally occupy the cation sites of Ga of host material. MBE growth of multi-layer structures i.e. InGaGdNIGaN multiple-quantum well (MQW) was also carried out and its characteristic were investigated. The InGaGdNIGaN MQW samples showed clear hysteresis and clear saturation in the magnetization versus magnetic field curve with larger magnetization per unit volume than the InGaNIGaGdN MQW samples implying that carrier (electron) induced ferromagnetism occurs in such heterostructures. Better structural qualities have been achieved for the Si-doped barrier layers of InGaGdNIGaN samples in which more pronounced satellite peaks can be observed from the X-ray diffraction curves compared to the undoped barrier sample Adding Si in the barrier layers has further enhanced the ferromagnetic properties as well as electrical properties of the MQW structure samples. This work has provided useful experimentally based insights into GaN-based diluted magnetic semiconductors (DMSs), resulting in the development of semiconducting materials that show room temperature ferromagnetism. These materials could pave the way for development of multifunctional microelectronic devices that integrate electrical, optical, and magnetic properties particularly for the development of spin-based-electronic devices